From Cultural Tourism to Social Entrepreneurship: Role of Social Value Creation for Environmental Sustainability - Li, Xiaofeng; Abbas, Jaffar; Dongling, Wang; Baig, Noor Ul Ain; Zhang, Ruilian (Frontiers in Psychology, 2022)
Cross-cultural exchanges among the locals and the tourists have been beneficial in terms of social value creation and sustainability. The present study has examined the role of cultural tourism and social entrepreneurship on social value creation and environmental sustainability. The study has drawn a sample through a non-probabilistic convenience sampling method for desired data collection, as investigators approached tourists visiting the tourism destinations. The study reports data received with the help of tourists visiting cultural heritage in the Gilgit-Baltistan region of Pakistan. The study has employed the PLS_SEM approach for analysis purposes to draw the results. The findings showed a significant relationship between cultural tourism, environmental sustainability, and social value creation that significantly predicts environmental sustainability. The results revealed a significant positive association between social entrepreneurship, social value creation, and environmental sustainability. Besides, results showed that social value creation mediates the relationship between cultural tourism and environmental sustainability and social entrepreneurship and environmental sustainability. The study's findings climax the importance of cross-cultural interactions that enriches the cultural understanding and gives new perspectives to the existing cultural traditions. Pursuing environmental sustainability through social value creation requires an excellent combination of the administrative and political collaborative strategy that integrates cultural tourism and social entrepreneurship in tourist destination development and aims to attain improved tourist attractions. Besides, this research identifies a significant effect of cultural tourism on environmental sustainability. However, the relationship between tourism and environmental sustainability is bidirectional. It might provide direction for further study. The findings deliver valuable insight into global cultural tourism and social entrepreneurship activities that provide tourism destinations for community development. This investigation produces a systematic and holistic research framework to help explore the influence of cultural tourism and social value creation on the environmental sustainability at tourism destinations. The generalizability of the findings supplies helpful directions for future research on environmental sustainability related to social entrepreneurship and cultural tourism that leads to social value creation.